1991
DOI: 10.1172/jci114965
|View full text |Cite
|
Sign up to set email alerts
|

Loss of endothelium-dependent relaxant activity in the pulmonary circulation of rats exposed to chronic hypoxia.

Abstract: To determine whether exposure to chronic hypoxia and subsequent development of pulmonary hypertension induces alterations of endothelium-dependent relaxation in rat pulmonary vascular bed, we studied isolated lung preparations from rats exposed to either room air (controls) or hypoxia (H) during 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
160
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(169 citation statements)
references
References 29 publications
7
160
2
Order By: Relevance
“…19 Endothelium-dependent and -independent vasodilation was determined as dose-dependent reduction in pulmonary arterial pressure (⌬P PA ) in response to ACh and sodium nitroprusside (SNP), respectively, in lungs preconstricted with U4661951. 20 Pulmonary and systemic hemodynamics were measured in vivo in CHF and control rats as described, 8,14 and the vasorelaxant effect of inhaled nitric oxide was determined as dose-dependent reduction in P PA . Western blot analyses from whole lung homogenate and fresh lung endothelial cells (FLECs) and immunohistochemical analyses were performed as outlined in the Online Data Supplement.…”
Section: Methodsmentioning
confidence: 99%
“…19 Endothelium-dependent and -independent vasodilation was determined as dose-dependent reduction in pulmonary arterial pressure (⌬P PA ) in response to ACh and sodium nitroprusside (SNP), respectively, in lungs preconstricted with U4661951. 20 Pulmonary and systemic hemodynamics were measured in vivo in CHF and control rats as described, 8,14 and the vasorelaxant effect of inhaled nitric oxide was determined as dose-dependent reduction in P PA . Western blot analyses from whole lung homogenate and fresh lung endothelial cells (FLECs) and immunohistochemical analyses were performed as outlined in the Online Data Supplement.…”
Section: Methodsmentioning
confidence: 99%
“…As in other cardiovascular diseases, endothelial dysfunction in models of pulmonary arterial hypertension is established when pulmonary arteries exhibit a decrease in the relaxant response to acetylcholine, the reference endothelium-dependent vasodilator, acting through the activation of endothelial muscarinic receptors coupled to NO production [4,5]. In a mouse model of chronic hypoxia-induced pulmonary arterial hypertension, we have shown that the relaxant response induced by the β 2 -AR stimulation, which is also endothelium-and eNOSdependent, is preserved, whereas the relaxant response to acetylcholine is decreased [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…An increased propensity to PHT in the newborn period, compared with other stages of life, is predominantly related to two factors: a failure in the physiological fall in pulmonary vascular resistance required for a successful transition to postnatal life, and the rapid development of anatomical changes in the heart and pulmonary vasculature (23), known collectively as vascular remodeling. Evidence suggests that abnormally decreased pulmonary arterial relaxation is an early functional feature of PHT that directly contributes to the subsequent anatomical changes of remodeling (1). Together, these changes lead to narrowing of the vessel lumen, exaggerated responses to constrictors (3,14), and reduced compliance, all of which are believed to contribute to a chronic and progressive form of PHT that is refractory to current therapies (13).…”
mentioning
confidence: 99%